The Gambia : Demand for Broad Money and Implications for Monetary Policy Conduct - Sriram, Subramanian (IMF Working Papers; Working Paper ;, 2009)
This paper evaluates the demand for broad money (M2) in The Gambia for January 1988-June 2007. There appears to be a long-run relationship for demand for real M2, but the relationship is not stable. Exogenous output shocks, financial innovation, changes in income velocity, and inadequate data quality contribute to the instability. The authorities may need to apply the monetary targeting regime flexibly in the overall objective of preserving price stability. A possible option for The Gambia is to become an inflation targeter lite.